AB0762 Relationship of the six minute walking test and quality of life in patients with systemic sclerosis. (12th June 2018) - Cuomo, G.; GJELOSHI, K.; Masini, F.; Danzo, F.; Romano, C.; Adinolfi, L.E.
Abstract : Background: The six minute walking test (6MWT) is a standardised measure of submaximal exercise capacity. It is a surrogate measure of heart and lung involvement. There are no studies on relationship between 6MWT and quality of life evaluated by Short form 36. Objectives: To evaluate the relationships between of the 6 min walking distance (6MWD) and each items of SF36 Methods: Fifty consecutive SSc patients were investigated. They underwent 6MWT and complete the SF-36 (assessed the 8 domains of the questionnaire as well as the physical component score-PCS and mental component score-MCS). Results: 6MWD ranged from 253 to 582 (median 420); we listed the correlations from 6MWT and only the statistically significant features of SSc and the items of SF36 Age: median 48 (range 20–72); Rho −0.51; p<0.00001 EScSG Activity Index: median 0.5 (range 0–5); Rho −0.33; p0.009 HAQ-DI: median 0.375 (range 0–2.275); Rho −0.26; p 0.048 mRSS: median 2 (range 0–17); Rho-0.35; p0.007 Pulmonary hypertension (echocardiography): median 30 (range 13–80); Rho −0.26; p 0.048 SF36: PCS: median 43 (range 20–65); Rho 0.41; p 0.0016 PF: median 75 (Range 0–100); Rho 0.40; p 0.002 GH: median 50 (range 10–92); Rho 0.43; p 0.0007 Conclusions: Our study first demonstrates that 6MWT is correlated to some aspects of quality of life as measured by SF36 in the SSc patients. This results must been considered when assessing 6MWT in SSc. References: [1] Schoindre Yet al, J Rheumatol2009. [2] Flahertyet al, Am J Respir Crit Care Med2006 [3] Casanova C. et al, Eur respire J2007 Disclosure of Interest: None declared